The Role Of Acmeology In Shaping And Developing The Professional Competence Of Educators And Other Specialists - Bibikhadicha Babanazarovna Kunnazarova (Indonesian Journal Publisher, 2025)
This article examines the role of acmeology theory and practice in shaping and developing the professional competence of teachers and other specialists. First, the emergence of acmeology, its key principles, and approaches aimed at achieving high personal and professional goals are outlined. Next, intervention methods such as acmeological trainings, mentoring, reflective sessions, and self-development programs are reviewed, with their effectiveness illustrated by examples. Finally, the potential of acmeological approaches for the professional growth of teachers and various specialists is highlighted, and practical recommendations are provided.